К вопросу о влиянии ислама на взаимоотношения Пакистана с государствами центральной Азии - Крыжко, Е.В. (Культура народов Причерноморья, 2014)
Пакистан выступает активным сторонником объединения мусульманских стран в едином
союзе. Роль ислама во внешней политике Пакистана в отношении государств Центральной Азии и
Афганистана трансформировалась от объединяющей к отталкивающей, что было связанно с
беспокойством и настороженностью руководства как центральноазиатских государств, так и ИРП в
вопросе распространения исламистской угрозы с территории Афганистана. Центральноазиатские
политические элиты считали «Талибан» основной угрозой собственной безопасности, а
поддерживающий его Пакистан, соответственно, воспринимали как скрытого врага. Пакистан виступає активним прихильником об’єднання мусульманських країн в єдиному
союзі. Роль ісламу в зовнішній політиці Пакистану щодо держав Центральної Азії і Афганістану
трансформувалася від об’єднуючої до відразливої, що було пов’язано із занепокоєнням та
настороженістю керівництва як центральноазіатських держав, так і ІРП в питанні розповсюдження
ісламістської загрози з території Афганістану. Центральноазіатські політичні еліти вважали
«Талібан» основною загрозою власній безпеці, а підтримуючий його Пакистан, відповідно, сприймали як
прихованого ворога. Pakistan is an active supporter of the association of Muslim countries in a single union. Pakistani
leaders, starting with M. Zia-ul-Haq (served as President 1978 – 1988) never lost sight of the Islamic factor,
often approach to solving international problems of considering precisely this factor. Growth of Islamism in
Pakistan contributed to tensions in its relations with India, the absence of any trade-offs on the Kashmir issue.
The theory of "Islamism" has an important place in the foreign policy of Pakistan. The existence of this theory is
due to the fact that the IRP was created as a Muslim state, and in multinational Pakistan Islam is seen as a
unifying factor. First steps guide the independent states of Central Asia, testified that they did not intend to build
its foreign policy strategy solely on the ideas of Islamic solidarity and tend to develop in the first place the
economic component of relations with new partners. Central Asian political elites considered "Taliban" main
threat to its security and its supporting Pakistan, respectively, was seen as a hidden enemy.
The Islamic factor in the foreign policy of Pakistan with regard to the countries of Central Asia and Afghanistan
has been transformed from a unifying role in repelling that was associated with anxiety and alertness
management as the Central Asian states, and the IRP in the issue of the spread of Islamist threat from
Afghanistan.